THE EFFECT OF DIET CONTAINING HIGH ALPHA-LINOLENIC ACID ON OMEGA-3 FATTY ACIDS AND HEALTH STATUS OF THE HEART IN BROILERS - Lilik Retna Kartikasari; Robert Hughes; Mark Geier; Robert Gibson (Buletin Peternakan, 2017)
The objectives of the study were to examine the effect of diet high in alpha-linolenic acid (ALA) on omega-3 long chain polyunsaturated fatty acids (n-3 LCPUFA) and the health status of the heart. Diets were based on a commercial starter diet, with a low level of fat. The experimental diets contained two levels of ALA (2.23 and 19.37%), with the total fat content was approximately 5%. Pure or blended vegetable oils were included at a level of 2.8% in order to produce diets with the desired levels of linoleic acid (LA) and ALA. The ratio of LA to ALA of the diets  was  9.75:1 for control diet and 1.37:1 for high ALA diet. Each diet was provided ad libitum for the duration of the 28-d growth period. At 28 days of age, six selected birds from each pen (12 birds per group) were weighed individually and hearts were collected for analysis. A ratio of right ventricle mass (RV) to total ventricle mass (TV) was used to indicate the health status of the heart. Results showed that dietary treatment increased the level of ALA from 0.1% (control diet) to 0.5% (P<0.01). Increasing levels of dietary ALA raised the level of n-3 LCPUFA and total n-3 in heart tissues by 4-5-fold. There was no significant difference observed in the level of heart LA, arachidonic acid (AA) and total n-6. The increased levels of dietary ALA did not cause changes in the ratio of RV to total TV. In conclusion, it appears clear that based on our data, increasing ALA content in the diet of chickens could potentially be beneficial for the health of the birds; however, further work is necessary.